Liver injury after pulsed methylprednisolone therapy in multiple sclerosis patients. Issue 6 (4th May 2018) - Nociti, Viviana; Biolato, Marco; De Fino, Chiara; Bianco, Assunta; Losavio, Francesco Antonio; Lucchini, Matteo; Marrone, Giuseppe; Grieco, Antonio; Mirabella, Massimiliano
Abstract: Objectives: High‐dose pulsed methylprednisolone‐related liver injury cases have been reported in the literature, but a prospective study in patients with multiple sclerosis (MS) has never been performed. The aim of this study was to evaluate the prevalence and severity of liver injury in patients with MS after pulsed methylprednisolone therapy. Methods: We performed a prospective observational single‐center study on patients with MS treated with i.v. methylprednisolone 1, 000 mg/day for 5 days. We tested the liver functionality before and 2 weeks after the treatment. In case of severe liver injury, defined according to "Hy's law, " a comprehensive hepatologic workup was performed. Results: During a 12‐month observation period, we collected data on 251 cycles of i.v. steroid treatment of 175 patients with MS. After excluding eight cycles presenting a basal alteration of the biochemical liver tests, we observed a prevalence of 8.6% of liver injury in MS patients treated with pulsed methylprednisolone for clinical and neuroradiological relapses. In 2.5% of the patients, the liver injury was severe according to Hy's law; after a comprehensive hepatologic workup, three of them received a diagnosis of drug‐induced liver injury and the other three of autoimmune hepatitis. Conclusions: Liver injury after pulsed methylprednisolone therapy in patients with MS is not infrequent, and a close monitoring of aminotransferase level before treatment and 2 weeks later seems advisable. Abstract : This a prospective observational single‐center study on patients with multiple sclerosis, in relapsing phase of the disease, treated with i.v. methylprednisolone 1, 000 mg/day for 5 days. We tested liver function tests before treatment and after 2 weeks. During 12‐month observation period, we collected 251 cycles of i.v. high‐dose steroid treatment from 175 patients (65.1% females). Serum aminotransferase elevation (any grade) was observed on twenty‐one cycles 2 weeks after methylprednisolone therapy (prevalence 8.6%). Six of them (prevalence 2.5%) presented a severe liver injury according to Hy's law. Liver injury should be considered a possible adverse event in patients with multiple sclerosis treated with pulsed methylprednisolone therapy for clinical relapse. Aminotransferase monitoring after pulsed methylprednisolone treatment is useful for clinical management.